Tandem metathesis depolymerization and cyclopolymerization toward flexible–rigid block copolymers with unique damping properties. Issue 24 (31st May 2022) - Zhang, Lingli; Quan, Ying; Wang, Hao; Han, Huijing; Liao, Xiaojuan; Sun, Ruyi; Xie, Meiran
Abstract : Triblock copolymers containing shortened natural rubber segments and polyacetylene segments were synthesized by tandem metathesis depolymerization and cyclopolymerization, and modified by triazolinedione toward unique damping properties. Abstract : Metathesis depolymerization (MDP) of natural rubber (NR) was readily conducted to afford depolymerized NR ( d NR x ) bearing a living chain end, which can initiate metathesis cyclopolymerization (MCP) of 1, 6-heptadiyne monomers to yield conjugated polyacetylene (PA) derivatives, and thus block copolymers consisting of a rubbery d NR x segment and a plastic PA segment were achieved by this newly constructed tandem MDP–MCP strategy. Importantly, triblock copolymers containing a flexible d NR x segment and rigid ionic PA segment possessed good mechanical properties, and exhibited distinctive damping performance with a unique relaxation plateau covering a broad temperature range, which could be further enhanced by modifying triblock copolymers with bromo-functionalized triazolinedione derived from biobased oleic acid. Therefore, the developed MDP–MCP method should become a feasible technique with expanded applications in the remodeling of unsaturated polymers for providing flexible–rigid functional block copolymers.